KOMUNIKASI KRISIS PT. JOUSKA FINANSIAL INDONESIA DALAM PEMULIHAN CITRA PERUSAHAAN - Isyraqi Khairy Siregar; Kurniati Putri Haeirina (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Jouska is an independent financial advisory company that provides offline and online consulting services that recently went viral in social media and had a strong brand image as a financial consultant related to today's needs. In July 2020, social media was outraged by the complaint, which claimed to have been harmed by them, because Jouska allegedly directed their clients to determine an Investor Fund Account Management Contract (RDI) with PT Mahesa Strategies Indonesia, whose shares are affiliated with Jouska. However, during the development, the client experienced a significant loss in the shares. This situation turned out to be similar complaints from other clients until Jouska underwent a crisis that led to the government's blocking, and the case ended in the realm of law. This study aims to analyze the communication that presents Image Restoration Theory through a lens. The method used in this research is descriptive qualitative, and it was found that Jouska did not yet have a clear SOP for communication with clients and had not implemented crisis management appropriately. There are several recommendations that Jouska can achieve to restore public trust, including collaborative action with various parties, building a communication strategy, and optimal media relations.